Christian Arabic versions of Daniel : a comparative study of early MSS and translation techniques in MSS Sinai Ar. 1 and 2 - Hjalm, Miriam L. (Biblia Arabica, 2016)
In Christian Arabic Versions of Daniel , Miriam L. Hjälm provides an insight into the Arabic transmission of the biblical Book of Daniel. This book offers an inventory and a classification of extant manuscripts as well as a detailed account of the translation techniques employed in the early manuscripts. The use of the texts is discussed and the various versions are compared with liturgical Bible material. Miriam L. Hjälm shows the importance of Arabic as a tool for understanding the development of the religious heritage of Christian communities under Muslim rule. Arabic became an indispensable part of the everyday life of many Near Eastern Christians and was increasingly used next to the established liturgical languages, which remained the standard measure of the biblical text.